A Critical Look at Cultural Criticism by Dr. Abdollah Ghazami - Yusef Hamid Jaber (دراسات في اللغة العربيّة وآدابها)
The book, Cultural Criticism, aims to discover literary patterns which comprise the current cultural infrastructure. The author uses a critical approach which is different from the established literary criticism, which limits itself to exploring the beauties of literary texts and ignores the central but not so apparent themes. Therefore, cultural criticism is necessary so that these cultural patterns and themes as well as the styles of the works become known. These styles are interwoven with social styles and norms and it is these norms and styles that help or hinder their expansion. This article examines the most important themes of this book and attempts to suggest modifications to its approaches and methods.